Respuesta :

Answer:

  • x = -5
  • y = 5

Step-by-step explanation:

  • => -7x - 2y = 25

            -4x - 9y = -25

  • => 4(-7x - 2y = 25)

             7(-4x - 9y = -25)

  • => -28x - 8y = 100

            -28x - 63y = -175

  • => 55y = 275
  • => y = 5

Now, let's substitute the value of y into the first equation.

  • => -7x - 2y = 25
  • => -7x - 2(5) = 25
  • => -7x - 10 = 25
  • => -7x = 35
  • => x = -5

Now, let's check our answer to make sure our answer is correct.

Check:

  • -4x - 9y = -25
  • => -4(-5) - 9(5) = -25
  • => 20 - 45 = -25
  • => -25 = -25

Hence, this is proved correct.

Hoped this helped.

[tex]BrainiacUser1357[/tex]